Indicators to evaluate agricultural nitrogen efficiency of the 27 member states of the European Union. (July 2016) - Godinot, O.; Leterme, P.; Vertès, F.; Carof, M.
Highlights: Three novel nitrogen indicators were tested at the national scale. The nitrogen indicators are relevant tools for comparing agricultural systems. Studying their change over time provides useful information to decision makers. Including changes in soil N increased indicator uncertainty. Potential N efficiency was assessed for EU-27 countries. Abstract: Nitrogen (N) use in European agriculture is not efficient, with less than one third of available N recovered in intended outputs. Over two thirds of N is lost to the environment, where it has negative ecological, social and economic consequences. Improving N efficiency in crop and animal production is a priority to reduce its detrimental effects while maintaining food production. The territory scale is particularly suitable for evaluation of N efficiency because it is used for environmental impact assessment and public policies. However, N Use Efficiency (NUE), the efficiency indicator available at this scale, has several limitations: (i) inputs and outputs can vary depending on the boundaries and definitions used, (ii) input production and transport are not always included, and (iii) changes in soil N stock are rarely considered. Three indicators were recently developed at the farming system scale to overcome NUE limitations. System N efficiency (SyNE) expresses N in intended outputs as a function of all major N inputs and losses. Relative N efficiency (RNE) expresses N efficiency relatively to its potential given the nature of productions. System N balance (SyNB) expresses N losses from cradle to the gate of the farm. All three indicators include N losses due to the production and transport of inputs and soil N stock variations. The current study tested these indicators at the national scale to provide a better understanding of N management in 27 European countries. The study demonstrates the feasibility and utility of calculating these indicators at the national scale. The mean NUE of European countries is 0.35, while their mean SyNE is 0.23, highlighting the importance of considering soil N loss in efficiency indicators. Average SyNB is 113 kgN ha −1 AA, but varies from 31 to 432 kgN ha −1 AA, showing the large margin of progress of some countries regarding N losses. Mean RNE is 0.43, which means that European countries could maintain their production with much less N inputs. The systems approach enables relevant comparisons among countries with different production methods and intensities. Combining SyNE and SyNB provides complementary information about the agricultural use of N resources and the resulting environmental pressure. RNE assesses the progress margin of each country based on its production and enriches the efficiency analysis by considering the nature of agricultural products. These indicators are promising tools to study, compare and improve the N efficiency of territories or countries.